BACK ANALYSIS OF LOWWAL SLOPE FAILURE PT XYZ, CENTRAL KALIMANTAN PROVINCE - Farhan Rizqia, Muhammad
One of main component in open pit mining is slope stability. The stability of slopes which is located at open pit must be analyzed to prevent failure that might be happened. PT XYZ is a coal mining company which is located in Central Kalimantan Province. In one of the pit at PT XYZ, failure occurred on crest part of the lowwall slope. Determination about causative factor on lowwall clope PT XYZ is done with back analysis method and analysis of lowwall existing slope stability and Life of Mine (LOM) at PT XYZ is done. Process from back analysis of failure is using RS2 software for determine causative factor of failure. Back analysis process is done with varying condition of material strength and groundwater level at slope design until Strength Reduction Factor (SRF) result below 1. After knowing the causative factor of the failure, slope stability analysis of existing lowwall slope and Life of Mine (LOM) is done using Slide software. Design of slope stability analysis is done with valuating the value Factor of Safety (FoS) and Probability of Failure (PoF). The result of slope stability analysis will be compared with provision of Kepmen ESDM Nomor 1827K/30/MEM/2018. Back analysis result shows that the condition of lowwall slope when failure have 66% of strength failure and groundwater level at the top of the joint that resulting SRF value 0,99. The result of existing slope stability analysis shows that the slope is safe with FoS static and dynamic value in consecutive are 1,6 and 1,42, and also PoF value is 0%. The result of LOM stability analysis shows that the slope is unsafe with FoS static and dynamic value in consecutive are 0,9 and 0,79, and also PoF value is 100%. From the result of LOM design analysis, the design recommendation is given with relocating river stream at slope crest and minimizing the angle of LOM overall slope with 2o. The result of recommendation shows that the FoS static and dynamic value in consecutive are 1,33 and 1,13, and also PoF value is 0%.